The Importance of Physiotherapy: Enhancing Health and Well-being - Nancy Sharma (International Journal of Orthopedic Nursing and Practices, 2023)
Physiotherapy is an essential aspect of healthcare that emphasizes the recovery and upkeep of physical functionality, mobility, and overall health. This article explores the significance of physiotherapy in promoting optimal health and its impact on various conditions and populations. The review of literature highlights different therapeutic approaches employed in physiotherapy and their effectiveness. The discussion encompasses the wide range of benefits provided by physiotherapy, including pain management, injury prevention, rehabilitation, and improvement of overall quality of life. The article concludes by emphasizing the essential role of physiotherapy in enhancing physical function and promoting holistic well-being.
Keywords: Health; Rehabilitation; mobility; pain management; physiotherapy